(untitled) (Grande Medical Journal, 2019)
Introduction: Our institution is tertiary care centre and referral centre for spine surgery. We like to share the epidemiological parameters of the case treated here. Methods: This is retrospective, descriptive study conducted from 2013 to August 2018. All the data retrieved from hospital information system of admitted patients and demographic presentations, disease pattern, region of involvement were analyzed. Result: There were a total of 698 patients. Male were 262(37.5%) and female were 436(62.5%). Age wise distribution ranged from 2 years to 85 years. Maximum numbers of patients were from 31 to 60 years (57.5%) and there were only 3% of cases less than 15 years and above 76 years. 30.2% cases were related to trauma, 29.8% of cases were related to disc pathology, followed by degenerative diseases 13%, infection 9.2%, and 5.4% were of tumors 8.7 % were cases were not classified in the above categories. There were 56.7% cases from lumbosacral region, 16.3% cases from thoracic region, 13.2% cases from cervical region, 5.7% cases were from multiple regions. 0.3% were of generalized nature which could not be classified. Conclusion: Spinal diseases are more common in female population, more frequent in third to sixth decade of life. Highest numbers of cases were from traumatic cause followed by degenerative disc diseases. Lumbosacral region is most commonly affected.